Development of a peptide-based fluorescent probe for biological heme monitoring. Issue 3 (21st December 2018) - Newton, Laura D.; Pascu, Sofia I.; Tyrrell, Rex M.; Eggleston, Ian M.
Abstract : A prototype peptide-based probe has been developed for the determination of intracellular heme levels. Abstract : Heme plays a vital role in cell biology and dysregulation of heme levels is implicated in a wide range of diseases. However, monitoring heme levels in biological systems is currently not straightforward. A short synthetic peptide probe containing 7-azatryptophan is shown to bind hemin in vitro with quenching of the azatryptophan fluorescence. This chemical tool can be used to detect the change in free heme induced in human skin cells upon exposure to UVA irradiation.